PERBANDINGAN DAYA HAMBAT EKSTRAK DAUN KAYU MANIS (CINNAMOMUM BURMANNII) KONSENTRASI 10% DAN 20% TERHADAP PERTUMBUHAN JAMUR DERMATOFITA PADA PASIEN TINEA KORPORIS SECARA IN VITRO - FITRI DYANA SIAGIAN; MELVIANA LUBIS (JURNAL ILMIAH SIMANTEK, 2020)
Dermatophytosis is one of the superficial dermatomycosis groups caused by dermatophyte fungal infections of the skin,occurring as a reaction of the host to fungal metabolite products and due to invasion by an organism in a living tissue.Cinnamomum burmannii leaves have an antifungal effect on fungi. Flavonnoids, saponins, alkaloids, and tannins on theleaves of cinnamon are known to inhibit dermatophytic fungi. This type of research is an experimental research because inthis study the treatment was carried out, namely the administration of cinnamon leaf extract (Cinnamomun burmannii) with aconcentration of 10% and 20% and then the effect on the growth of dermatophytic fungi will be seen. This study uses a staticgroup comparative research method (Static Group Comparison) that is by making measurements (observations) made afterthe treatment group accepts the program or intervention. From the results of the study showed that the leaves of cinnamon(Cinnamomum burmannii) with a concentration of 10% and 20% can inhibit the growth of Microsporum sp. In the fourthpatient. Cinnamomun burmannii leaf extract with a concentration of 10% and 20% has the ability as an antifungal to thegrowth of microsporum sp. in the fourth patient and cinnamon burmannii leaf extract 20% concentration was the mosteffective in inhibiting the growth of microsporum sp. (highest clear zone).